IMPLEMENTATION OF AUGMENTED REALITY IN MOTORCYCLES INTRODUCTION LEARNING - Sri Rahayu; Vernanda Adhitya Darmawan; Fitri Nuraeni; Dewi Tresnawati (Informatika, Universitas Jenderal Soedirman, 2022)
Augmented reality technology in the field of education can be used as an interactive learning media that can minimize boredom during the conventional teaching and learning process, namely by using books containing text and pictures.The advantages of augmented reality technology, it can be used to explain basic motorcycle introduction materials, which usually require a complete explanation not only from writing and pictures. Therefore, this study aims to create an interactive learning media for motorcycle engine introduction based on augmented reality. The method used in this learning media is Research and Development consisting of needs analysis, design design, design implementation, testing, expert validation, media revision, feasibility test, media improvement, and product. The results of this study are interactive learning media applications that display 3-dimensional objects regarding motorcycle engines using audio explanations for each of the existing 3-dimensional objects, as well as adding a quiz feature to increase interactivity in the teaching and learning process.